Autophagy-Associated Shrinkage of the Hepatopancreas in Fasting Male Macrobrachium rosenbergii Is Rescued by Neuropeptide F - Thongrod, Sirorat; Wanichanon, Chaitip; Kankuan, Wilairat; Siangcham, Tanapan; Phadngam, Suratchanee; Morani, Federica; Isidoro, Ciro; Sobhon, Prasert (Frontiers in Physiology, 2018)
Invertebrate neuropeptide F-I (NPF-I), much alike its mammalian homolog neuropeptide Y, influences several physiological processes, including circadian rhythms, cortical excitability, stress response, and food intake behavior. Given the role of autophagy in the metabolic stress response, we investigated the effect of NPF-1 on autophagy during fasting and feeding conditions in the hepatopancreas and muscle tissues of the male giant freshwater prawn M. rosenbergii. Starvation up-regulated the expression of the autophagy marker LC3 in both tissues. Yet, based on the relative levels of the autophagosome-associated LC3-II isoform and of its precursor LC3-I, the hepatopancreas was more responsive than the muscle to starvation-induced autophagy. Injection of NPF-I inhibited the autophagosome formation in the hepatopancreas of fasting prawns. Relative to the body weight, the muscle weight was not affected, while that of the hepatopancreas decreased upon starvation and NPF-1 treatment could largely prevent such weight loss. Thus, the hepatopancreas is the reserve organ for the nutrient homeostasis during starvation and NPF-I plays a crucial role in the balancing of energy expenditure and energy intake during starvation by modulating autophagy.